2019
DOI: 10.1111/jonm.12847
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between feedback environment established by mentor and nurses’ career adaptability: A cross‐sectional study

Abstract: Aim The aim of this study was to explore nurses’ feedback seeking, the contextual issues established by mentors and career adaptability in a Chinese context. In addition, this research explored the moderating role of nurses’ political skill. Background Mentors play a direct, important and distinct role in supporting mentees. However, little is known about the relationship between the contextual elements of mentor feedback and nurses’ career adaptability. Design This study was based on cross‐sectional data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Interpersonal relationships in an organization are relationships established in the organization with the goal of work interests, usually including subordinate relationships and peer relationships, which can promote career development by exchanging resources, and can also give emotional support (Sheikhi et al., 2016 ). Interpersonal interaction has a very important impact on career development (Bozionelos, 2003 ; Gong & Li, 2019 ; Yi & Tjosvold, 2010 ). Nurses should pay attention to the establishment of interpersonal relationships in the organization and give a strong support system for their career development.…”
Section: Discussionmentioning
confidence: 99%
“…Interpersonal relationships in an organization are relationships established in the organization with the goal of work interests, usually including subordinate relationships and peer relationships, which can promote career development by exchanging resources, and can also give emotional support (Sheikhi et al., 2016 ). Interpersonal interaction has a very important impact on career development (Bozionelos, 2003 ; Gong & Li, 2019 ; Yi & Tjosvold, 2010 ). Nurses should pay attention to the establishment of interpersonal relationships in the organization and give a strong support system for their career development.…”
Section: Discussionmentioning
confidence: 99%
“…According to the social exchange theory, there is an exchange relationship between people; when individuals receive help and support from others, they tend to pay it forward in return (Wilson et al, 2010). Studies have shown that supportive feedback environment helps to improve employe role clarity, job satisfaction and performance, as well as the professional adaptability of nurses (Gong and Li, 2019). Volunteers view support from their organization, family, and friends as a kind of potential pressure and driving force of development, and as such, they try their best to respond with their own altruistic actions.…”
Section: The Joint Moderated Effect Of Role Identification and Perceimentioning
confidence: 99%
“…Therefore, in order to strengthen and promote voluntary service, it is necessary to continue researching ways to improve the psychological wellbeing of volunteers. However, previous studies on volunteers focused on volunteer motivation and function (Arbak and Villeval, 2013;Dickson et al, 2013Dickson et al, , 2015Erasmus and Morey, 2016;Li et al, 2016), voluntary incentive and management (Prestby et al, 1990;Edwards, 2007;Dickson et al, 2013;Gong, 2018;King, 2018), volunteerism and values (Beverley, 1975;Johnson et al, 1998;Misener et al, 2009;Shen et al, 2019), and leisure perspective (Stebbins, 1996;Green and Chalip, 2004). Only a few studies have looked at psychological mechanisms that influence volunteering (Spector and Fox, 2002;Kang et al, 2007;Fornyth, 2010;Chacón et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the findings also suggest that energizing the team’s process should be considered for enhanced performance in teams. When a safe environment is ready, members facilitate learning from failures ( Hirak et al, 2012 ), and members’ feedback-seeking behavior and adaptability could be strengthened ( Gong and Li, 2019 ). Therefore, leaders can take a strategy that promotes a psychologically safe climate and stimulates interaction, regardless of external support at a team level.…”
Section: Implications For Practicementioning
confidence: 99%